SoTL in Latin America: Bridging Cultures, Transforming Teaching and Learning - Jerez Yañez, Oscar; Maldonado Mahauad, Jorge; Schwartzman, Gisela; Rodriguez Enríquez, Carolina; Montoya Sandí, Sugey; Herrera Alcaíno, Álvaro; Del Mastro Vecchione, Cristina; Morales-Chan, Miguel; Díaz Pérez, Wendy; Mogollón de Lugo , Ivory; Camargo De Luque, Gina; Martínez Barrientos, Alejandra; et al. (Teaching and Learning Inquiry, 2025)
ABSTRACT The Scholarship of Teaching and Learning (SoTL) is rapidly emerging as a transformative force in Latin American higher education, bridging diverse cultures and reshaping pedagogical practices to meet the region’s unique challenges. Inspired by Paulo Freire’s critical pedagogy—which emphasizes education as a means of social transformation and empowerment—this article examines how SoTL integrates interculturality, identity, and equity into university education across Latin America. By aligning teaching and learning with the rich sociocultural realities of the region, SoTL effectively addresses educational inequalities and promotes inclusive access to learning opportunities. Institutions have embraced innovative practices such as faculty development programs, the integration of SoTL methodologies across various disciplines, and active student participation in pedagogical innovation. National policies and regional collaborations, notably the formation of LatinSoTL, have further propelled this movement, fostering a culture of reflective practice and continuous improvement. Despite significant advancements, challenges remain. These include the cultural integration of SoTL concepts, heavy faculty workloads, limited interdisciplinary programs, technological disparities, and the imperative to align educational practices with the Sustainable Development Goals (SDGs). Overcoming these obstacles requires sustained efforts in faculty development, investment in technological infrastructure, and supportive policies that recognize and reward teaching excellence. The impact of SoTL is evident in the growing valuation of teaching, increased student engagement, and policy shifts that prioritize teaching in academic evaluations. By embracing SoTL and the principles of Freire’s critical pedagogy, Latin American institutions not only improve educational outcomes, but also contribute valuable insights to the global discourse on higher education. This article highlights the critical role of culturally responsive education in transforming teaching and learning, ultimately bridging cultures and fostering social change throughout the region. RESUMEN La investigación académica sobre la docencia y el aprendizaje (scholarship of teaching and learning, SoTL) está emergiendo rápidamente como una fuerza transformadora en la educación superior latinoamericana, estableciendo puentes entre diversas culturas y reformulando las prácticas pedagógicas para enfrentar los desafíos particulares de la región. Inspirado en la pedagogía crítica de Paulo Freire—la cual enfatiza la educación como una vía hacia la transformación social y el empoderamiento—este artículo analiza cómo SoTL integra la interculturalidad, la identidad y la equidad en la educación universitaria a lo largo de América Latina. Al alinear la enseñanza y el aprendizaje con las complejas realidades socioculturales regionales, SoTL aborda eficazmente las desigualdades educativas y promueve un acceso inclusivo a las oportunidades de aprendizaje. Diversas instituciones han adoptado prácticas innovadoras, tales como programas de desarrollo académico para docentes, la integración de metodologías SoTL en múltiples disciplinas y la participación activa de estudiantes en innovaciones pedagógicas. Las políticas nacionales y colaboraciones regionales, particularmente mediante la conformación de redes como LatinSoTL, han impulsado aún más este movimiento, fomentando una cultura de práctica reflexiva y mejora continua. Pese a estos importantes avances, subsisten diversos desafíos. Entre ellos destacan la integración cultural de los conceptos de SoTL, la sobrecarga laboral docente, la limitada disponibilidad de programas interdisciplinarios, las brechas tecnológicas y la necesidad de alinear las prácticas educativas con los Objetivos de Desarrollo Sostenible (ODS). Superar estos obstáculos requiere esfuerzos sostenidos en la formación docente, inversión en infraestructura tecnológica y políticas institucionales que reconozcan y recompensen la excelencia en la enseñanza. El impacto del SoTL se evidencia en la creciente valoración de la docencia, un mayor compromiso estudiantil y cambios en políticas institucionales que priorizan la docencia en las evaluaciones académicas. Al adoptar el enfoque del SoTL y los principios de la pedagogía crítica freireana, las instituciones latinoamericanas no solo mejoran los resultados educativos, sino que además aportan valiosas perspectivas al discurso global sobre la educación superior. Este artículo enfatiza el rol esencial de la educación culturalmente sensible para transformar los procesos de enseñanza y aprendizaje, promoviendo el diálogo intercultural y favoreciendo el cambio social en toda la region.